Integrated Assessment of Industrial Effluent Impacts on Water Quality and Ecological Risks in Ona River, Ibadan, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Degradation of freshwater resources within Nigeria’s industrial zones threatens ecosystems and human health. This study examined the Ona River in Ibadan’s Oluyole Industrial Area through physicochemical, nutrient, heavy metal, and bacteriological analyses. Water samples from upstream, industrial discharge points, and a downstream residential site were collected in June 2024 and analyzed using standard protocols by the American Public Health Association (apha). Results showed elevated levels of Total Dissolved Solids (TDS) (0.73- 3.48 mg/L), Electrical Conductivity (EC) (119- 328 µS/cm), Biological Oxygen Demand (BOD₅) (9.2- 37.4 mg/L), and Chemical Oxygen Demand (COD) (2.9- 57.1 mg/L), with Dissolved Oxygen (DO) below 2.6 mg/L. Manganese levels (0.71- 0.93 mg/L) exceeded WHO (0.08 mg/L) and Nigerian standards (0.2 mg/l), while magnesium (17.7- 31.2 mg/L) surpassed FAO irrigation guidelines (0.2 mg/l). Water Quality Index (WQI) rated industrial sites as poor (43.2- 48.9) and the residential site as moderate (54.4). Trace coliforms downstream (0.001 cfu/mL) indicated occasional contamination. These findings highlight effluent discharge's role in water degradation, emphasizing the need for industrial pretreatment, standards aligned with FAO and WHO, and continuous multi-parameter monitoring to protect ecosystems.